Minimally-Invasive Assisted Robotic Spine Surgery (MARSS) - Pérez de la Torre, Ramiro A.; Ramanathan, Siddharth; Williams, Ashley L.; Perez-Cruet, Mick J. (Frontiers in Surgery, 2022)
Minimally-invasive assisted robotic spine surgery (MARSS) has expanded the surgeons armamentarium to treat a variety of spinal disorders. In the last decade robotic develop in the spine surgical arena has improved safety, accuracy and efficacy of instrumentation placement. Additionally, robots have been applied to remove “difficult to get to” tumors while allowing minimally invasive access. Gross manual movements by the surgeon are translated into fine precision movements by the robot. This is exemplified in this chapter with the use of the da Vinci robot to remove apical thoracic tumors. In what we have called minimal-assisted robotic spine surgery or MARSS, we will review the develop, latest technology, and case review using MARSS to treat spine pathology in a minimally invasive fashion.